Nitrile‐converting enzymes: An eco‐friendly tool for industrial biocatalysis. (24th October 2013) - Ramteke, Pramod W.; Maurice, Navodita G.; Joseph, Babu; Wadher, Bharat J.
Abstract: Nitriles are organic compounds bearing a CN group; they are frequently known to occur naturally in both fauna and flora and are also synthesized chemically. They have wide applicability in the fields of medicine, industry, and environmental monitoring. However, the majority of nitrile compounds are considered to be lethal, mutagenic, and carcinogenic in nature and are known to cause potential health problems such as nausea, bronchial irritation, respiratory distress, convulsions, coma, and skeletal deformities in humans. Nitrile‐converting enzymes, which are extracted from microorganisms, are commonly termed nitrilases and have drawn the attention of researchers all over the world to combat the toxicity of nitrile compounds. The present review focuses on the utility of nitrile‐converting enzymes, sources, classification, structure, properties, and applications, as well as the future perspective on nitrilases.